The participation of women in the Solomon Islands education system : a study with particular reference to Solomon Island women who held New Zealand government tertiary scholarships between 1973 and 1990 : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Development Studies at Massey University - Quinn, Marion (Massey University, 1994)
This is a study on the participation of women in the Solomon Islands education system, focussing in particular on the experiences of Solomon Islands women who held New Zealand Government tertiary scholarships between 1973 and 1990. Despite increasing international recognition of the importance of education for girls and women in addressing critical national economic and social goals, gender remains the single most significant determinant of access to schooling in most developing countries. While there is a growing body of literature on factors affecting the participation of girls and women in education in developing countries, little has been written on the subject in relation to the South Pacific and nothing of substance in relation to Solomon Islands. More generally, Altbach (1985) noted the lack of research on the experience of women as overseas students and the outcomes of tertiary education for women in developing countries. The findings of this study confirm research carried out elsewhere that the socio-economic status of parents has greater influence on the schooling of girls than of boys. For the earliest women tertiary students, the encouragement of educated fathers was of particular significance in breaking down traditional barriers to girls' participation in education. Girls and women from matrilineal societies were, in general, given greater encouragement to enter and to remain longer in school. In undertaking tertiary study overseas and returning to positions of responsibility in both the public and private sectors, the women in this study were in many ways 'trailblazers' for the women who followed behind them. Their position was not an easy one, subject often to personal misunderstanding and criticism as they sought a new role and a new status for women in Solomon Islands society. Yet this was not an elite, Westernised group, divorced from their own society. Those interviewed were characterised by a strong commitment to assisting other Solomon Islands women and to contributing effectively to the development of their society. The study concludes that the interests of development have been well served by the investment in their education.
Keywords: Women; Solomon Islands; Education; Social conditions; Economic conditions